Surface Fermi contours and phonon anomalies at the surface of the random alloy. (12th July 2021) - Okada, Michio; Rotenberg, Eli; Kevan, S D; Schäfer, J; Plummer, E W
Abstract: The impact of compositional disorder on physical properties is a subject of prime focus in many materials systems. In this paper, we report photoemission measurements of Mo1− x Re x (110)-(1 × 1)H alloy surfaces to probe the relationship between the surface Fermi contours and giant Kohn anomalies observed in the surface phonon dispersion relations. Our measured nesting vectors precisely predict the composition dependence of the anomalous wave vectors.